Working From Home and Job Loss Due to the COVID-19 Pandemic Are Associated With Greater Time in Sedentary Behaviors - McDowell, Cillian P.; Herring, Matthew P.; Lansing, Jeni; Brower, Cassandra; Meyer, Jacob D. (Frontiers in Public Health, 2020)
Objectives Due to the COVID-19 pandemic, major changes to how, or even whether, we work have occurred. This study examines associations of changing COVID-19-related employment conditions with physical activity and sedentary behaviour. Methods Data from 2,303 US adults in employment prior to COVID-19 were collected April 3rd-7th, 2020. Participants reported whether their employment remained unchanged, they were working from home (WFH) when they had not been before, or they lost their job due to the pandemic. Validated questionnaires assessed physical activity, sitting time, and screen time. Linear regression quantified associations of COVID-19-related employment changes with physical activity, sitting time, and screen time, controlling for age, sex, race, BMI, smoking status, marital status, chronic conditions, household location, public health restrictions, and recalled physical activity, sitting time, and screen time prior to the COVID-19 pandemic. Results Compared to those whose employment remained unchanged, participants whose employment changed (either WFH or lost their job) due to COVID-19 reported higher sitting time (WFH: g=0.153, 95% CI=0.095 to 0.210; lost job: g=0.212, 0.113 to 0.311) and screen time (WFH: g=0.158, 0.104 to 0.212; lost job: g=0.193, 0.102 to 0.285). There were no significant group differences for physical activity (WFH: g=-0.030, -0.101 to 0.042; lost job: g=-0.070, -0.178 to 0.037). Conclusion COVID-19 related employment changes were associated with greater sitting and screen time. As sedentary time is consistently negatively associated with current and future health and wellbeing, increased sedentary time due to employment changes is a public health concern.